Analysis of Teacher Competencies in Physical Education Learning Achievement - Mochammad Al Nathaniel Hendriawan Nathan; Anggi Setia Lengkana; Respaty Mulyanto (STKIP Muhammadiyah Kuningan, 2023)
This study aimed to determine how effective physical education teachers were in learning achievement for public elementary school students, especially for elementary schools in Tanjung Sari District. Because to undergo the teaching profession, several competencies must be possessed, namely pedagogical competence, professional competence, personal competence, and social competence. This study used a qualitative descriptive method with a natural setting or naturalistic inquiry design. The researcher conducted the research by conducting interviews with a sample of teachers in public elementary schools, and the data collection techniques used were observation, interviews, and documentation. In analyzing the data, researchers used data triangulation. From the research that has been done, data indicates that the teacher has attempted to master the four competencies, which include 1) mastery of the material, 2) class management, 3) learning variety, 4) teaching style, 5) social interaction, 6) Be well behaved. It can be stated that most physical education teachers in the Tanjung Sari sub-district are competent. In the minority, some teachers are still in the evaluation stage to develop these four competencies.